Coarse‐grained debris flow dynamics on erodible beds. Issue 3 (14th March 2017) - Lanzoni, Stefano; Gregoretti, Carlo; Stancanelli, Laura Maria
Abstract: A systematic set of flume experiments is used to investigate the features of velocity profiles within the body of coarse‐grained debris flows and the dependence of the transport sediment concentration on the relevant parameters (runoff discharge, bed slope, grain size, and form). The flows are generated in a 10 m long laboratory flume, initially filled with a layer consisting of loose debris. After saturation, a prescribed water discharge is suddenly supplied over the granular bed, and the runoff triggers a debris flow wave that reaches nearly steady conditions. Three types of material have been used in the tests: gravel with mean grain size of 3 and 5 mm, and 3 mm glass spheres. Measured parameters included: triggering water discharge, volumetric sediment discharge, sediment concentration, flow depth, and velocity profiles. The dynamic similarity with full‐sized debris flows is discussed on the basis of the relevant dimensionless parameters. Concentration data highlight the dependence on the slope angle and the importance of the quasi‐static friction angle. The effects of flow rheology on the shape of velocity profiles are analyzed with attention to the role of different stress‐generating mechanisms. A remarkable collapse of the dimensionless profiles is obtained by scaling the debris flow velocity with the runoff velocity, and a power law characterization is proposed following a heuristic approach. The shape of the profiles suggests a smooth transition between the different rheological regimes (collisional and frictional) that establish in the upper and lower regions of the flow and is compatible with the presence of multiple length scales dictated by the type of contacts (instantaneous or long lasting) between grains. Key Points: Granular‐liquid flow velocity profiles observed in flume experiments collapse if normalized by runoff velocity Dynamic similarity with field debris flows are reproduced in the laboratory with moderated scale effects associated with the reduced geometrical scale Granular‐liquid flows over erodible beds show a spatially varied rheology consequent to the presence of different stress‐generating mechanisms